Confounding underlies the apparent month of birth effect in multiple sclerosis. Issue 6 (2nd July 2013) - Fiddes, Barnaby; Wason, James; Kemppinen, Anu; Ban, Maria; Compston, Alastair; Sawcer, Stephen
<x xml:space="preserve">Abstract</x> Objective Several groups have reported apparent association between month of birth and multiple sclerosis. We sought to test the extent to which such studies might be confounded by extraneous variables such as year and place of birth. Methods Using national birth statistics from 2 continents, we assessed the evidence for seasonal variations in birth rate and tested the extent to which these are subject to regional and temporal variation. We then established the age and regional origin distribution for a typical multiple sclerosis case collection and determined the false‐positive rate expected when comparing such a collection with birth rates estimated by averaging population‐specific national statistics. Results We confirm that seasonality in birth rate is ubiquitous and subject to highly significant regional and temporal variations. In the context of this variation we show that birth rates observed in typical case collections are highly likely to deviate significantly from those obtained by the simple unweighted averaging of national statistics. The significant correlations between birth rates and both place (latitude) and time (year of birth) that characterize the general population indicate that the apparent seasonal patterns for month of birth suggested to be specific for multiple sclerosis (increased in the spring and reduced in the winter) are expected by chance alone. Interpretation In the absence of adequate control for confounding factors, such as year and place of birth, our analyses indicate that the previous claims for association of multiple sclerosis with month of birth are probably false positives. ANN NEUROL 2013;73:714–720